Current diversity of fish fauna in the middle reach of the Chu River (Eurasian Journal of Ecology, 2016)
Current diversity of fish fauna was investigated in the middle reach of the Chu River. 27 fish species were revealed here in all. Simpson, Shennon and Sorensen’s indexes were used for fish diversity description and comparison. Big differences in fish composition were revealed for the different sites. Weak resemblance was observed for the different ages in the same site even. Roach Rutilus rutilus, dace Leuciscus leuciscus, gudgeon Gobio lepidolaemus, and grey stone loach Triplophysa dorsalis were the most abundant fish species. In comparison with the earlier data, the results of 2012 and 2013 revealed depletion of fish diversity in the middle reach of the Chu River. Many factors could impact on fish diversity here, but changes natural hydrological regime and unpractical use of water.
Keywords: ichthyofauna; transboundary; diversity; community; indigenous; alien.